The Arabidopsis Mitochondrial Protease FtSH4 Is Involved in Leaf Senescence via Regulation of WRKY-Dependent Salicylic Acid Accumulation and Signaling - Zhang, Shengchun (Plant Physiol, 2017)
Mitochondria and autophagy play important roles in the networks that regulate plant leaf senescence and cell death. However, the molecular mechanisms underlying the interactions between mitochondrial signaling and autophagy are currently not well understood. This study characterized the function of the Arabidopsis (Arabidopsis thaliana) mitochondrial AAA-protease gene FtSH4 in regulating autophagy and senescence, finding that FtSH4 mediates WRKY-dependent salicylic acid (SA) accumulation and signaling. Knockout of FtSH4 in the ftsh4-4 mutant resulted in severe leaf senescence, cell death, and high autophagy levels. The level of SA increased dramatically in the ftsh4-4 mutant. Expression of nahG in the ftsh4-4 mutant led to decreased SA levels and suppressed the leaf senescence and cell death phenotypes. The transcript levels of several SA synthesis and signaling genes, including SALICYLIC ACID INDUCTION DEFICIENT2 (SID2), NON-RACE-SPECIFIC DISEASE RESISTANCE1 (NDR1), and NONEXPRESSOR OF PATHOGENESIS-RELATED PROTEINS1 (NPR1), increased significantly in the ftsh4-4 mutants compared with the wild type. Loss of function of SID2, NDR1, or NPR1 in the ftsh4-4 mutant reversed the ftsh4-4 senescence and autophagy phenotypes. Furthermore, ftsh4-4 mutants had elevated levels of transcripts of several WRKY genes, including WRKY40, WRKY46, WRKY51, WRKY60, WRKY63, and WRKY75; all of these WRKY proteins can bind to the promoter of SID2. Loss of function of WRKY75 in the ftsh4-4 mutants decreased the levels of SA and reversed the senescence phenotype. Taken together, these results suggest that the mitochondrial ATP-dependent protease FtSH4 may regulate the expression of WRKY genes by modifying the level of reactive oxygen species and the WRKY transcription factors that control SA synthesis and signaling in autophagy and senescence.